2021
DOI: 10.20961/lar.v19i3.50932
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using fermented lime (Citrus aurantifolia) waste powder (FLWP) on performance, lymphoid organs, and heterophil/lymphocyte ratio of broiler chickens

Abstract: <p class="MDPI17abstract"><strong>Objective: </strong>Fermented lime waste had potential value as a feed additive for poultry. A Bioactive compound such as citric acid in the lime waste can improve the broiler's performance and body resistance. The study purposed to evaluate the effect of using fermented lime waste powder (FLWP) on the broiler performance and body resistance.</p><p class="MDPI17abstract"><strong>Methods: </strong>This study used 200 female broiler stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…In this case, using fermented banana peel instead of maize as a conventional energy source for broiler chickens can reduce the use of maize. In line with this, Shihah et al [70] reported that using fermented lime (Citrus aurantifolia) peels up to 3% in diets had no significant effect on the growth, feed intake, and FCR of broiler chickens. Indeed, the administration of fermented lime (C. aurantifolia) peels improved broiler immune competencies, as evidenced by a greater relative weight of the Fabricius bursa than the control.…”
Section: Fermentationmentioning
confidence: 84%
“…In this case, using fermented banana peel instead of maize as a conventional energy source for broiler chickens can reduce the use of maize. In line with this, Shihah et al [70] reported that using fermented lime (Citrus aurantifolia) peels up to 3% in diets had no significant effect on the growth, feed intake, and FCR of broiler chickens. Indeed, the administration of fermented lime (C. aurantifolia) peels improved broiler immune competencies, as evidenced by a greater relative weight of the Fabricius bursa than the control.…”
Section: Fermentationmentioning
confidence: 84%